Factors Restraining Communication Patterns Among Islamic Education Institutions in the Development of Islamic Symbolism in Lhokseumawe City - Misran Fuadi; Sukiman Sukiman; Rubino Rubino (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
The Islamic Sharia Service, Ulama Consultative Council, and Office of the Ministry of Religion are integral to Lhokseumawe City's Islamic syar'im operations and broadcasts. These three institutions helped Lhokseumawe City build Islamic emblems.The Islamic Sharia Service, Ulama Consultative Council, and Ministry of Religion were researched. The three informants were chosen because they could describe their experiences and opinions on the topic, which was institutional communication in the construction of Islamic symbols in Lhokseumawe City.The Islamic Syriac Service and Dayah Education, Ulema Consultative Council, and Lhokseumawe City Office of the Ministry of Religion use interpersonal, group, and organizational communication patterns to carry out religious symbolism of many things. so religious programs can be successfully comprehended and conducted.Mutual support and cooperation, as well as establishing a pattern of communicating with the object of concurrent activity, can overcome obstacles in coordinating and implementing various Islamic propagation activities due to different agencies and leadership. Each institution has the budget and administrative responsibility, but equally in the development of Islamic symbols that the community can feel.